Importance of main pancreatic duct dilatation in IPMN undergoing surveillance. Issue 13 (14th August 2018) - Marchegiani, G; Andrianello, S; Morbin, G; Secchettin, E; D'Onofrio, M; De Robertis, R; Malleo, G; Bassi, C; Salvia, R
Abstract: Background: The association between risk of pancreatic cancer and a dilated main pancreatic duct (MPD) in intraductal papillary mucinous neoplasm (IPMN) is debated. The aim of this study was to assess the role of MPD size in predicting pancreatic cancer in resected IPMNs and those kept under surveillance. Methods: All patients with IPMN referred to the Pancreas Institute, University of Verona Hospital Trust, from 2006 to 2016 were included. The primary endpoint was the occurrence of malignancy detected at surgery or during follow-up. Results: The final cohort consisted of 1688 patients with a median follow-up of 60 months. Main pancreatic duct dilatation was associated with other features of malignancy in both the resected and surveillance groups. In patients who underwent resection, only a MPD of at least 10 mm was an independent predictor of malignancy. In patients kept under surveillance, MPD dilatation was not associated with malignancy. Fifteen of 71 patients (21 per cent) with malignancy in the resection cohort had a dilated MPD alone, whereas only one of 30 (3 per cent) under surveillance with MPD dilatation alone developed malignancy. Patients with a dilated MPD and other worrisome features had an increased 5-year cumulative incidence of malignancy compared with those with a non-dilated duct (11 versus 1·2 per cent; P < 0·001); however, the risk of malignancy was not significantly increased in patients with a dilated MPD alone (4 versus 1·2 per cent; P = 0·448). Conclusion: In patients under surveillance, a dilated MPD alone was not associated with an increased incidence of malignancy in IPMN. Abstract : Duct dilatation no risk alone